Plasmatic Dimethylarginines in Dogs With Myxomatous Mitral Valve Disease - Valente, Carlotta; Guglielmini, Carlo; Baron Toaldo, Marco; Romito, Giovanni; Artusi, Carlo; Brugnolo, Laura; Contiero, Barbara; Poser, Helen (Frontiers in Veterinary Science, 2021)
Plasmatic dimethylarginines, asymmetric dimethylarginine (ADMA) and symmetric dimethylarginine (SDMA) are considered biomarkers of endothelial and renal dysfunction, respectively, in humans. We hypothesize that plasmatic concentration of dimethylarginines in dogs with myxomatous mitral valve disease (MMVD) is influenced by heart disease stage. Eighty-five client-owned dogs with MMVD, including 39, 19, and 27 dogs in ACVIM stages B1, B2, and C+D, respectively, and a control group of 11 clinically healthy dogs were enrolled. A prospective, multicentric, case-control study was performed. Each dog underwent a complete clinical examination, arterial blood pressure measurement, thoracic radiography, six-lead standard electrocardiogram, transthoracic echocardiography, CBC, biochemical profile, and urinalysis. Plasmatic concentration of dimethylarginines was determined through high-performance liquid chromatography coupled with tandem mass spectrometry. Median ADMA was significantly increased in dogs of group C+D (2.5 µmol/L [2.1-3.0]) compared to those of group B1 (1.8 µmol/L [1.6-2.3]; p < 0.001) and healthy dogs (1.9 µmol/L [1.7-2.3]; p = 0.02). Median SDMA was significantly increased in dogs of group C+D (0.7 µmol/L [0.5-0.9]) compared to those of groups B1 (0.4 µmol/L [0.3-0.5]; p < 0.001), B2 (0.4 µmol/L [0.3-0.6]; p < 0.01), and the control group (0.4 µmol/L [0.35-0.45]; p = 0.001). In the final multivariable analysis, ADMA and SDMA were significantly associated with left atrium to aorta ratio (p < 0.001), and creatinine (p < 0.001), respectively. Increased plasmatic concentrations of dimethylarginines suggest a possible role as biomarkers of disease severity in dogs with decompensated MMVD.